Community Barriers and Challenges in Adopting Digital Technology: A Case Analysis on Vulnerable Groups - Sukiman (Jayapangus Press, 2022)
This research aims to identify and analyze the barriers and challenges faced by vulnerable community groups in adopting digital technology. Vulnerable groups, such as the elderly, people with disabilities and rural communities, often encounter obstacles in harnessing the potential of digital technology in their daily lives. This research employs a qualitative method, involving in-depth interviews and secondary data analysis, to explore accessibility barriers, low digital literacy, as well as security and privacy issues faced by these vulnerable groups. Furthermore, the research also delves into their expectations for digital technology, such as access to information, economic empowerment, and better social connections. The findings of this research indicate that collective efforts from the government, private sector, non-profit organizations, and civil society are crucial to address these barriers and create greater digital inclusion. Digital inclusion is considered a key factor in building a fairer and more sustainable society in this digital era.